Left inferior accessory renal arteries its embryological basis and clinical significance - Satyanarayana, N; Guha, R; Nitin, V; Praveen, G; Datta, AK; Sunitha, P (Journal of College of Medical Sciences-Nepal, 2012)
The variations in origin of renal arteries are very common. During routine dissection of a male cadaver we found left accessory renal artery. The origin of accessory renal artery is immediately below main renal artery. The left inferior accessory renal arteries run towards inferior pole of left kidney, in the area where the left renal vein was leaving the left kidney. The vascular variations are very important for vascular surgeons, urologists, nephrologists, radiologists. DOI: http://dx.doi.org/10.3126/jcmsn.v7i1.5976 JCMSN 2011; 7(1): 65-68